Applied economics : an introductory course - Griffiths, Alan, 1944-; Wall, Stuart, 1946- (Harlow : Financial Times/Prentice Hall, 2004)
Revised and updated every two years, 'Applied Economics' provides students with a unique combination of theory and application relating to real world experiences and events. It gives clear information on the major issues facing the British economy.
Previous ed.: 2001.
Includes bibliographical references and index.
Keywords: Economics; Macroeconomics; International economics